Study on the High Temperature Friction and Wear Behaviors of Cu-Based Friction Pairs in Wet Clutches by Pin-on-Disc Tests - Er-Hui Zhao; Biao Ma; He-Yan Li (Advances in Materials Science and Engineering)
This work is devoted to the study of the high temperature friction and wear behaviors of Cu-based friction pairs in wet clutches under different temperatures, rotation speeds, and loads. Pin-on-disc tests are carried out on the UMT-3. The friction coefficient, wear factor, and high temperature wear mechanism are primarily analyzed. The results show that as the temperature rises from 120°C to 420°C, the friction coefficient increases from 0.28 to 0.35 at first and then decreases to 0.30, when the vibration of friction coefficient is significantly identified. Meanwhile, the wear factor grows gradually from K=7.9×10-8 g/Nm to K=41.8×10-8 g/Nm at first and then grows sharply to K=112.2×10-8 g/Nm. The main wear mechanisms are abrasive wear and ploughing wear when the temperature is below 345°C, and the wear seriously deteriorates when the temperature exceeds 345°C, when the wear mechanism changes to adhesive wear and delamination wear.